OPTIMIZATION OF THE STRUCTURAL DESIGN OF THE CHASSIS OF AN AUTOMATED GUIDE VEHICLE USING EXPERIMENTAL AND NUMERICAL METHODS - Danu Prasetyo; Sunaryo; Heru Nugroho; Budi Santoso (Clean Energy and Smart Technology, 2026)
Automated Guided Vehicles (AGVs) are a smart transportation solution that is increasingly being used in industry. The stability and strength of the chassis are critical factors in ensuring AGV performance when carrying loads. This study examines the effects of load variations and material types on the structural performance of AGV chassis through an experimental approach and numerical simulation based on Finite Element Analysis (FEA). The materials used were ASTM A36 and ASTM A500, with loads of 5 kg, 10 kg, and 15 kg. A chassis design with dimensions of 400 × 300 × 80 mm was modeled and analyzed using Computational Fluid Dynamics (CFD) software. Validation was performed through experimental testing using a dial indicator. The results show that at a 15 kg load, ASTM A500 experienced a maximum stress of 60.15 MPa and a deflection of 0.00078 m, lower than ASTM A36, which reached 68.06 MPa and a deflection of 0.00089 m. The difference between the simulation and experimental results was well below 10%. Similarly, regarding the safety factor, ASTM A500 has a value of 2.7145 at maximum load, indicating that this material has a higher safety margin compared to ASTM A36. Based on these results, ASTM A500 is considered more efficient and stable, and is more recommended for AGV chassis applications. This study highlights the importance of integrating numerical and experimental methods to produce optimal structural designs.